Pharmacoeconomic comparison of the second generation insulin analogs and insulins on their base - I. N. Dyakov; S. K. Zyryanov (Izdatelstvo OKI, 2021)
Effective control of Diabetes Mellitus (DM) is an actual task from clinical and economic points of view. The second generation insulin analogs increase level of DM compensation without hypoglycemia. The economic aspects of their usage have been evaluated early, but it is still actual due to changes in prices and new data about clinical efficacy were published.Materials and methods: Clinical-economic comparison of insulin glargine 300 U/ml (iGla 300), insulin degludec (iDeg) and insulin degludec/ insulin aspart (iDegAsp) in the Russian conditions has been performed in naïve patients' group as well as in the group of patients with previous insulintherapy. Number of patients with HbA1c <7 % was chosen as efficacy criterion. Direct and indirect costs (medications, treatment of CV-complications, GDP loses etc.) were indicated and calculated based on the constructed model.Results: iGla 300 can give an economy till 20 % for medication cost and till 10 % for direct medical expenditures in compare with iDeg in DM Type 1. For both patients' groups iGla 300 can save 10-23 % of sources in compare with iGed and iDegAsp in DM Type 2. In DM2T iGla 300 had more efficacy and less cost in compare with iDeg in elderly patients with renal insufficiency.Conclusion: An effective control of DM with modern insulins is profitable from government position of payment due to decreasing expenditures for complications treatment.